Número e peso de perfilhos no pasto de capim-braquiária sob lotação contínua - Santos, Manoel Eduardo Rozalino; Fonseca, Dilermando Miranda da; Pimentel, Roberson Machado; Silva, Guilherme Portes; Gomes, Virgilio Mesquita; Silva, Simone Pedro Da [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2011)
The experiment was conducted to study the relationship between the number and weight of tiller categories in Brachiaria decumbens cv. Basilisk pasture managed under continuous stocking with cattle. The pasture was managed with an average height of about 25 cm. Plants of four different heights (10, 20, 30 and 40 cm) were evaluated by means of the randomized block design with two replications. The number of vegetative tillers, both live and total, reduced linearly according to the plant height. The number of reproductive tillers increased linearly according to pasture plant height (from 8 to 84 tillers m-2 when comparing plants 10 to 40 cm high). Vegetative and reproductive tiller weight increased linearly according to pasture plant height. Vegetative tiller weight (0.316 g average) was lower than the reproductive tiller weight (0.401 g average). A linear and negative relationship was found between the number and weight of the vegetative tillers, whereas a linear and positive one was found for the reproductive tillers. There are fewer vegetative tillers, and a greater number of reproductive and dead tillers in places with tall plants. At the places with high B. decumbens plants, tillers are heavier.

Objetivou-se estudar a relação entre o número e o peso de categorias de perfilhos em pasto de Brachiaria decumbens cv. Basilisk sob lotação contínua com bovinos. O pasto foi manejado com altura média de aproximadamente 25 cm. Foram avaliadas quatro alturas de plantas no mesmo pasto (10, 20, 30 e 40 cm), em delineamento de blocos ao acaso, com duas repetições. Os números de perfilhos vegetativos, vivos e totais reduziram linearmente com a altura da planta. O número de perfilho reprodutivo aumentou de forma linear com a altura da planta (de 8 para 84 perfilhos m-2 quando se comparam plantas de 10 a 40 cm). Os pesos dos perfilhos vegetativos e reprodutivos incrementaram linearmente com a altura da planta. O peso do perfilho vegetativo (0,316 g, em média) foi menor do que o peso do perfilho reprodutivo (0,401 g, em média). A relação entre o número e o peso do perfilho vegetativo foi linear e negativa, enquanto que essa relação, para o perfilho reprodutivo, foi linear e positiva. Em locais com plantas altas há menor número de perfilhos vegetativos, bem como maior número de perfilhos reprodutivos e mortos. Nos locais mais altos do pasto de B. decumbens os perfilhos são mais pesados.
Number and weight of tillers in signalgrass pasture under continuous stocking
Keywords: Brachiaria decumbens; número de perfilho; perfilho reprodutivo; perfilho vegetativo; peso de perfilho; Brachiaria decumbens; tiller number; reproductive tiller; vegetative tiller; tiller weight